(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2018)
In this article, the author presents the most important economic indicators on Saudi Arabian imports and exports in the 1970s and 1980s. This is the time when Saudi Arabia was growing rich and experiencing an oil boom.